Associations of novel 24-h accelerometer-derived metrics with adiposity in children and adolescents - Dygrýn, Jan; Medrano, María; Molina-Garcia, Pablo; Rubín, Lukáš; Jakubec, Lukáš; Janda, David; Gába, Aleš (Environmental health and preventive medicine, 2021)
BACKGROUND: Further research is required to explore the associations between 24-h movement behaviours and health outcomes in the paediatric population. Therefore, this study aimed to examine the associations between novel data-driven 24-h activity metrics and adiposity among children and adolescents. METHODS: The sample included 382 children (8-13 years) and 338 adolescents (14-18 years). The average acceleration (AvAcc) of activity, intensity gradient (IG), and metrics representing the initial acceleration for the most active time periods of the 24-h cycle were calculated from raw acceleration data. Adiposity measures included body mass index z-score, fat mass percentage (FM%), and visceral adipose tissue (VAT). Data analysis was performed using multiple linear regression adjusted for wear time, sex, maternal education level, and maternal overweight and obesity. RESULTS: Children demonstrated higher values in all 24-h activity metrics than did adolescents (p < 0.001 for all). For children, the initial acceleration for the most active 2, 5, 15, and 30 min of the 24-h cycle were negatively associated with FM% (p ≤ 0.043 for all) and VAT (p <0.001 for all), respectively. For adolescents, the IG was negatively associated with FM% (p = 0.002) and VAT (p = 0.007). Moreover, initial acceleration for the most active 2, 5, 15, 30, 60, and 120 min were associated with FM% (p ≤ 0.007 for all) and with VAT (p ≤ 0.023 for all). CONCLUSIONS: The intensity distribution of activity and initial acceleration for the most active 2, 5, 15, 30, 60, and 120 min within the 24-h cycle are beneficial for the prevention of excess adiposity in the paediatric population.
Keywords: Humans; Accelerometer; dítě; Child; Female; lidé; Adiposity; Health; ženské pohlaví; Male; Adolescent; akcelerometrie; Youth; Czech Republic; Accelerometry; Cross-Sectional Studies; Body composition; Exercise; Measurement; Česká republika; mužské pohlaví; cvičení; adipozita; průřezové studie; mladiství